2021
DOI: 10.3389/fvets.2021.728538
|View full text |Cite
|
Sign up to set email alerts
|

Different Non-cage Housing Systems Alter Duodenal and Cecal Microbiota Composition in Shendan Chickens

Abstract: Housing systems are among the most important non-genetic factors affecting hen production performance and intestinal microbes. With increased interest in animal welfare, cage-free laying hen housing systems have become common, providing behavioral freedom and health benefits. The present study aimed to compare the effects of plastic net housing system (NRS) and floor litter housing system (LRS) on the composition and function of the duodenal and cecal microbiota in Shendan chicken, one of the most popular layi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In addition, the Ruminococcaceae in the horse gut have also been proved to have immunomodulatory and anti-inflammatory effects ( 56 ). Ruminococcaceae_UCG-005 showed a significantly positive correlation with eggshell strength and egg weight, presumably achieved by increasing feed conversion in laying hens ( 57 ). Ruminococcaceae_UCG_005 also has a potent cellulolytic capacity ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Ruminococcaceae in the horse gut have also been proved to have immunomodulatory and anti-inflammatory effects ( 56 ). Ruminococcaceae_UCG-005 showed a significantly positive correlation with eggshell strength and egg weight, presumably achieved by increasing feed conversion in laying hens ( 57 ). Ruminococcaceae_UCG_005 also has a potent cellulolytic capacity ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the level of the most abundant genera, the abundance of Lactobacillus was higher in hens from HC than in hens from LC and MC, while the abundance of Bacteroides was the lowest in birds from MC. Lactobacillus is considered an important probiotic in the intestine of animals and is conductive to digestion and immunity [37], and was reported to be more highly abundant in the caecum of chickens who exhibited better health status [38]. The higher abundance of Lactobacillus in hens from HC may related to the larger space allowance and lower crowding stress, while oxidative stress could be induced by the crowding in smaller cages to promote pathogenic bacteria and reduce Lactobacillus [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Various reasons can be thought of when considering the causes of changes in egg components depending on the housing systems. For example, it is known that intestinal bacterial flora was modulated by environmental conditions such as different exercise stimuli [46] and that different housing systems change the microbiota in chickens [47,48]. Wan et al [48] have reported differences in the cecal and duodenal microbiota compositions of Shendan chickens reared in different non-cage housing systems (plastic net housing system and floor litter housing system).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is known that intestinal bacterial flora was modulated by environmental conditions such as different exercise stimuli [46] and that different housing systems change the microbiota in chickens [47,48]. Wan et al [48] have reported differences in the cecal and duodenal microbiota compositions of Shendan chickens reared in different non-cage housing systems (plastic net housing system and floor litter housing system). This may indicate that different housing systems change the microbiota, which affects digestibility, nutrient absorption, metabolism, and egg formation.…”
Section: Discussionmentioning
confidence: 99%